2019
DOI: 10.3390/su11113092
|View full text |Cite
|
Sign up to set email alerts
|

Linking Biophysical and Economic Assessments of Ecosystem Services for a Social–Ecological Approach to Conservation Planning: Application in a Biosphere Reserve (Biscay, Spain)

Abstract: The search for a balance between nature conservation and sustainable development remains a scientific and spatial planning challenge. In social-ecological systems based on traditional rural activities and associated with protected areas, this balance is particularly complex. Quantifying the economic impact of land use changes on ecosystem services can be useful to advise policy makers and improving social-ecological sustainability. In this study, we evaluated the land use changes in a time series and estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…First, the ES concept fits well within the BR focus on human–nature relationships and our approach of spatial assessment of ES values has rarely been undertaken in BRs. There are few studies that have mapped ES in biosphere reserves (but see Kermagoret & Dupras, 2018; Poikolainen et al., 2019), and even fewer that explicitly consider zonation in their analyses (but see Castillo‐Eguskitza et al., 2018, 2019). Second, we have used a participatory approach which is an important criterion of BR governance.…”
Section: Discussionmentioning
confidence: 99%
“…First, the ES concept fits well within the BR focus on human–nature relationships and our approach of spatial assessment of ES values has rarely been undertaken in BRs. There are few studies that have mapped ES in biosphere reserves (but see Kermagoret & Dupras, 2018; Poikolainen et al., 2019), and even fewer that explicitly consider zonation in their analyses (but see Castillo‐Eguskitza et al., 2018, 2019). Second, we have used a participatory approach which is an important criterion of BR governance.…”
Section: Discussionmentioning
confidence: 99%
“…Plieninger et al 2013;Cusens et al 2022). However, few studies have the BR zonation explicitly in their analyses (but see Castillo-Eguskitza et al 2019;Palliwoda et al 2021;Cusens et al 2022). Palliwoda et al (2021) explicitly mapped and analysed the differences in ES co-production across the zones of 137 European BRs finding that ES co-production does not always match with the objectives of zonation within BRs.…”
Section: Ecosystem Services In Unesco Biosphere Reservesmentioning
confidence: 99%
“…Palliwoda et al (2021) explicitly mapped and analysed the differences in ES co-production across the zones of 137 European BRs finding that ES co-production does not always match with the objectives of zonation within BRs. Castillo-Eguskitza et al (2019) mapped biophysical and monetary ES values in Urdaibai BR, Spain, and assessed the coincidence between the two value types within the BR zones. Although these two studies highlight the value of zonespecific ES valuation for assessing BR goals and objectives, both consider zones as an aggregate of each zone type (i.e.…”
Section: Ecosystem Services In Unesco Biosphere Reservesmentioning
confidence: 99%
“…The number of studies that consider the goods and services that ecosystems provide to human societies has increased over the last two decades [3][4][5]; however, there remains a need for strategies that take ESs provision into account in order to achieve a sustainable way of life for human societies and ecosystems [6]. Biophysical and socio-economic characterization is critical for informing decisions concerning the use, management, and administration of ecosystems [7]; however, experience has shown that exclusion of the perception of different stakeholders, along with their ties and interests, can lead to disagreements and even conflicts [8]. Perceptions of ESs depend on the environmental or ecological characteristics of the systems and on the cultural and socio-economic context [9,10].…”
Section: Introductionmentioning
confidence: 99%